BIOGRAPHY AND ECONOMIC THOUGHT OF IBN QAYYIM AL-JAWZIYYAH - Maulidizen, Ahmad; Bin Mohamad, Mohammad Taqiuddin (State Islamic University North Sumatra, 2018)
Abstrak: Biografi dan Pemikiran Ekonomi Ibn Qayyim al-Jawziyyah (691 H/1292 M–751 H/1350 M). Ibn Qayyim al-Jawziyyah dikenal sebagai salah satu tokoh terkemuka yang memiliki gagasan dalam pengembangan ekonomi Islam. Penjelasan ini menunjukkan urgensi meninjau kembali pemikiran dan gagasan Ibnu Qayyim al-Jawziyyah khususnya di bidang ekonomi. Dengan menggunakan metode analisis deskriptif kualitatif, artikel ini akan menganalisis biografi dan pemikiran ekonomi Ibn Qayyim al-Jawziyyah, seorang sarjana Muslim penting pada abad ke-13/14. Penulis menyimpulkan bahwa pemikiran Ibn Qayyim al-Jawziyyah di bidang ekonomi berimplikasi pada upaya mewujudkan konsep kesejahteraan sosial, pembentukan keadilan dan penghapusan ketidakadilan dalam kehidupan ekonomi.Abstract: Ibn Qayyim al-Jawziyyah is one of the prominent figures who had ideas in the development of Islamic economics. This explanation shows the urgency of re-examining the thoughts and ideas of Ibn Qayyim al-Jawziyyah especially in the economic field. Using a qualitative descriptive analysis method, this article will analyze the biography and economic thought of Ibn Qayyim al-Jawziyyah, a great Muslim scholar in the 13th/14th century. The authors emphasize that Ibn Qayyim al-Jawziyyah’s thought in the economic field implies mainly to realize the concept of social welfare, the formation of justice and the elimination of injustice in economic life.Keywords: Islamic economics, Ibn Qayyim al-Jawziyyah, Islamic history